Environment-Friendly Antiviral Agents for Plants - Song, Baoan; Jin, Linhong; Yang, Song.; Bhadury, Pinaki S.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Plant virus disease is a worldwide threat to agriculture. Environment-Friendly Antiviral Agents for Plants systematically describes the basic theory, new ideas, and new methods to discover novel antiviral agents through research on plant immune activation. The cutting-edge research methodology, technology and progress on novel antiviral agent innovation are systematically described. With abundant illustrations and figures, the book is intended for researchers and practitioners in the fields of pesticide science, plant protection, organic chemistry, fine chemicals, applied chemistry, environment chemistry and agriculture science. Dr. Baoan Song and Dr. Song Yang are professors at the Center for R&D of Fine Chemicals, Guizhou University, China; Mr. Linhong Jin and Dr. Pinaki S. Bhadury are associate professors there.
Studies on ?-Aminophosphonates with Antiviral Activity -- Synthesis, Characterization and Antiviral Activity of Cyanoacrylates and Derivatives -- Synthesis and Antiviral Activity of Chiral Thiourea Derivatives -- The Heterocyclic Antiviral Agents -- Innovation and Application of Environment-Friendly Antiviral Agents for Plants.
Keywords: Chemistry; Toxicology; Chemistry, Organic; Biochemistry; Proteomics; Plant diseases; Environmental chemistry; Chemistry; Organic Chemistry; Plant Pathology; Environmental Chemistry; Plant Biochemistry; Pharmacology/Toxicology.; Proteomics